#TITLE_ALTERNATIVE# - APRIANDI (NIM 12206059); Pembimbing: Prof. Dr.-Ing Ir. Rudi Rubiandini R.S., RIAN
Tracer is used in the oil industry in order to measure qualitatively or quantitatively how the fluid through the reservoir. Tracer can be used in a interwell test or a single well test. In interwell tests, tracer is injected in one well along with the carrier fluid (water in a waterflood or gas in gasflood) and detected after a while, which could have been from day-to-year. In a single well test, the tracer is injected into the formation of a well and then produced on the same wells. Tracer can be either radioactive or chemical, gas or liquid and has been used in the oil industry and hydrology for several decade. In the application of water injection, tracer is useful in improving reservoir modeling of computer systems through the breakthrough times, injector and producer relationships, thief zones and channeling. From this tracer injection data we will get real time breakthrough occurred in the field, which will be used to calibrate the existing reservoir model, to obtain a reservoir model that can represent the actual reservoir. With the field data we try to create scenarios to match the field data and reservoir models that we have. But the changes made here are limited to properties interwell injection wells and production wells which have had a tracer breakthrough.